An overview of students’ learning problems in hypothesis testing - Saras Krishnan; Noraini Idris (penerbit ukm, 2015)
Hypothesis testing is an important tool of statistical inference and is taught in most introductory Statistics Courses. However, students’ continuing struggle in making deep and connected understanding of the statistical concepts in the learning of hypothesis testing and its’ use is evidential from past studies. This article presents an overview of the problems faced by students in the learning of hypothesis testing. Understanding students’ learning of statistics in the introductory statistics courses are needed especially because introductory statistics courses have been the focus of statistics reform and because there has been great increase in the number of students in these courses in the recent years.